Bio-efficacy of Different Formulations of Chlorantraniliprole 0.53%+Fipronil 0.8% GR Against Yellow Stem Borer of Rice - Dhanapati, Gokul Krishna; Karjee, Mrinal; Sarkar, Prahlad (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted during rabi (December, 2020–May, 2021), and kharif (July–December, 2021) at University Instructional Farm, UBKV, Pundibari, Cooch Behar, West Bengal, India with a new combination of insecticides Chlorantraniliprole 0.53% w/w and Fipronil 0.8% w/w GR with different formulations to evaluate the bio-efficacy of these combinations of insecticides against yellow stem borer (Scirpophaga incertulas). In this study three formulations of Chlorantraniliprole 0.53% w/w+Fipronil 0.8% w/w GR @ 5.63 kg ha-1, @ 7.50 kg ha-1 and @ 9.38 kg ha-1 were used and Chlorantraniliprole 0.40% GR @ 1 kg ha-1, Fipronil 0.3% GR @ 25 kg ha-1, Cartap hydrochloride 4% GR @ 18.75 kg ha-1 and untreated control were evaluated against yellow stem borer in rice crop. The result suggested from the present investigation that Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 7.50–9.38 kg ha-1 was found best and effective as well as at par with each other against rice yellow stem borer. It has been observed that Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 9.38 kg ha-1 registered good yield, 4.81 t ha-1 and 4.72 t ha-1 which were on par with Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 7.50 kg ha-1 i.e., 4.79 t ha-1 and 4.70 t ha-1 in two consecutive seasons i.e., rabi, 2020–21 and kharif, 2021 respectively Whereas, Chlorantraniliprole 0.53%+Fipronil 0.8% GR @ 7.50 kg ha-1 found much suitable with effective, safe and favorable cost-benefit ratio. The study also showed that there was no significant difference in density of predators in treated and untreated plots.